Strategi Pemberdayaan Warga Gereja melalui Pelatihan Kewirausahaan Teknisi AC Residential bagi Jemaat GKI Depok - Yakub Hendrawan Perangin Angin (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
The need to carry out the responsibilities of the church's duties is one of them by empowering the congregation, empowerment of the congregation can be done one of them is through a program to improve the competence of human resources in this case the GKI Depok residents who need complete skills, knowledge and behavior. For this reason, the Residential AC Technician training program is an option that is not only in accordance with the needs of the church and the needs of the community in Depok but is also able to provide entrepreneurial business opportunities and become the seed of business units in the church environment, especially GKI Depok. The results of the training that took place from April 21-26, 2025 with 11 participants from the GKI Depok congregation were able to become examples and role models of the success of the congregation empowerment process in the GKI Depok environment which had a positive and long-term impact, even opening new opportunities to be able to carry out the professional certification process from the National Professional Certification Agency of the Republic of Indonesia and an incubator for other prospective new entrepreneurs. The PkM implementation method is carried out in the form of training and workshops.